(3fgL GdHdGZIs - (3Ydj Hf CHj WGdH,J (B40 (3g` s
(3ChdgG (B:s
(3CeG HYO GdMeO ddg GdPj LYd GdMeO KefkG dfYeGFg, heYGPG ef HdGFg aEfj cfJ aj YfahGf GdSf s
(3BNQgG (B:s
(3heG YSGg Cf jXgQ dfG HYV GdZehV, hjbY EdjfG HYO GdTPhP heG JhajbfG EdG HGddg hPdc aj QLH SfI CQHY eFg BNQ cJGH fgL GdHdGZI s
(3GdfSNI HgG MhGTs
(3fSNI NGeSIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3HghGeTgG JYdjbGJ hTQhM s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs